Risk Factors for Postoperative Bleeding after Adenoidectomy - Milan Urík; Michal Bartoš; Soňa Šikolová; Jana Jančíková; Klára Perceová; Jiří Jarkovský; Eva Klabusayová; Petr Štourač; Petr Jabandžiev (MDPI AG, 2021)
IMPORTANCE: Postoperative bleeding is a common and potentially life-threatening complication. Precise identification of risk factors in addition to the basic ones, such as coagulation parameters, is certainly very desirable. OBJECTIVE: The aim of this study was to identify other possible risk factors for bleeding after adenoidectomy in children. DESIGN: This observational prospective study enrolled children undergoing adenoidectomy from October 2019 to February 2020, then evaluated the influence of possible risk factors for bleeding. SETTING: Tertiary pediatric otorhinolaryngology center. PARTICIPANTS: A total of 288 children aged 0-18 years undergoing adenoidectomy for recurrent upper respiratory tract infections, recurrent acute otitis media, secretory otitis media, and obstructive sleep apnea syndrome. MAIN OUTCOMES AND MEASURES: Increased blood pressure and time of surgery were identified as risk factors for bleeding after adenoidectomy. RESULTS: Elevated systolic (p = 0.046), diastolic (p = 0.012), and mean arterial blood pressure (p = 0.007) (Mann-Whitney U test) as adjusted for age-specific distributions and with corrections for height and weight, as well as time length of surgery (p < 0.001) (Fisher's exact test) were revealed as statistically significant risk factors for postoperative bleeding. Atmospheric pressure, surgeon's level of experiences, chronic inflammatory content in adenoid vegetation (AV), size of AV, recidivism of AV, recurrent infections of the upper respiratory tract, type of anesthesia, long-term using of drugs, and positive coagulation questionnaire or pathology in standard coagulation tests were not found to be risk factors for bleeding after adenoidectomy. CONCLUSIONS AND RELEVANCE: In this prospective study within a well-defined population of children, we evaluated increased blood pressure and time of surgery as risk factors for bleeding after adenoidectomy. These data bring new information that complements current knowledge in this field.